(untitled) (REMUNOM, 2025)
The Access to Information Law (LAI), Law No. 12.527/2011, is a landmark in Brazilian public administration, consolidating the constitutional right to information and strengthening transparency and social control. Transparency in public management is an essential pillar of the Democratic Rule of Law, intrinsically linked to accountability and citizen participation. The LAI regulated the citizen’s right to request and obtain data on government action. However, its full implementation faces persistent challenges, such as the resistance of some bodies to provide information and the need to improve access mechanisms and clarity in data disclosure. This article seeks to examine the effectiveness of the LAI, identifying its advances and proposing improvements to strengthen the culture of openness and accountability in administration.